From Industrial to Social Campaigns: Lay Morality, General Elections and Australia’s Trade Union Federation - Caspersz, Donella; Barratt, Tom (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2020)
This article considers the potential for union revitalization through campaigning in general elections. It first charts changes in unions’ campaigns in general elections, moving beyond a focus on industrial relations issues towards issues of social significance, such as health and education. Second, by reconceptualizing this activity using lay morality, unions may enhance their ability to increase their power and legitimacy. Thus, by acting in this way, unions can broaden the bases for their legitimacy and build new opportunities for their renewal.However, this approach may not lead to revitalizing their density, but may open the opportunity for their renewal because this approach consolidates their legitimacy to a broader constituency. We suggest that when unions act in this way, they become agents of social utility who champion the interests of a wider constituency. We argue that, given the dynamics of changes to work and the ways in which workers now work, this provides one route for unions to tap into these multiple subjectivities of workers and remain relevant.This article combines an analysis of over 1000 media articles that cover four periods of campaigns by peak unions in Australian elections between the years 2007-2016, with original interviews with key informants and an analysis of electoral survey results for each election to provide the discussion. These three methods triangulate to establish the shift in unions’ campaign focus and to suggest that this is a potential path to revitalization.